Cardiomyopathies and a brief insight into DOX-induced cardiomyopathy - Sampat Singh Tanwar; Sumeet Dwivedi; Sheema Khan; Seema Sharma (The Egyptian Heart Journal)
Abstract Background Cardiomyopathy is a heterogeneous group of myocardial disorders characterized by structural and functional abnormalities of the heart muscle. It is classified into primary (genetic, mixed, or acquired) and secondary categories, resulting in various phenotypes including dilated, hypertrophic, and restrictive patterns. Hypertrophic cardiomyopathy, the most common primary form, can cause exertional dyspnea, presyncope, and sudden cardiac death. Dilated cardiomyopathy typically presents with heart failure symptoms, while restrictive cardiomyopathy is rarer and often associated with systemic diseases. Diagnosis involves a comprehensive evaluation including history, physical examination, electrocardiography, and echocardiography. Treatment options range from pharmacotherapy and lifestyle modifications to implantable cardioverter-defibrillators and heart transplantation in refractory cases. Main body Anthracyclines, particularly doxorubicin, have emerged as crucial components in cancer treatment, demonstrating significant antitumor activity across various malignancies. These drugs have become standard in numerous chemotherapy regimens, improving patient outcomes. However, their use is associated with severe cardiotoxicity, including cardiomyopathy and heart failure. The mechanisms of anthracycline action and toxicity are complex, involving DNA damage, iron-mediated free radical production, and disruption of cardiovascular homeostasis. Doxorubicin-induced cardiomyopathy (DIC) is a severe complication of cancer treatment with a poor prognosis and limited effective treatments. The pathophysiology of DIC involves multiple mechanisms, including oxidative stress, inflammation, mitochondrial damage, and calcium homeostasis disorder. Despite extensive research, no effective treatment for established DIC is currently available. Dexrazoxane is the only FDA-approved protective agent, but it has limitations. Recent studies have explored various potential therapeutic approaches, including natural drugs, endogenous substances, new dosage forms, and herbal medicines. However, the lack of experimental models incorporating pre-existing cancer limits the understanding of DIC pathophysiology and treatment efficacy. Conclusion Cardiomyopathy, whether primary or secondary, poses a significant clinical challenge due to its varying etiologies and poor prognosis in advanced stages. Anthracycline-induced cardiomyopathy is a severe complication of chemotherapy, with doxorubicin being a notable contributor. Despite advancements in cancer therapies, the cardiotoxic effects of anthracyclines necessitate further investigation into effective preventive strategies and therapeutic interventions to improve patient outcomes.